Planetary roller extruders in the sustainable development of polymer blends and composites – Past, present and future - Krzysztof Formela; Barış Eyigöz (eXPRESS Polymer Letters)
Screw extruders as continuous flow reactors allow the synthesis of new polymers, preparation of polymer blends and composites, and modification or functionalization of commercially available polymers. Literature data shows that the twin screw extrusion is the most popular solution used for this purpose. In contrast, the number of scientific papers on alternative methods, such as multi-screw extruders, is somewhat limited. This paper is the first review of the application of planetary roller extruders in the compounding and reactive processing of polymer blends and composites. To fill current knowledge gaps, we discuss the advantages and disadvantages of planetary roller extruders compared to other screw extruders. Moreover, we summarize recent advances in planetary roller extrusion in producing thermal sensitive and biodegradable polymeric materials, rubber compounds, materials for 3D printing, or plastics and rubber recycling. This work also proposes the possible scenarios for further sustainable development of polymer blends and composites using planetary roller extruders.